Sequence variations of the EGR4 gene in Korean men with spermatogenesis impairment - Se Ra Sung; Seung Hun Song; Kyung Min Kang; Ji Eun Park; Yeo Jung Nam; Yun-jeong Shin; Dong Hyun Cha; Ju Tae Seo; Tae Ki Yoon; Sung Han Shim (BMC, 2017)
Abstract Background Egr4 is expressed in primary and secondary spermatocytes in adult mouse testes and has a crucial role in regulating germ cell maturation. The functional loss of Egr4 blocks spermatogenesis, significantly reducing the number of spermatozoa that are produced. In this study, we examined whether EGR4 variants are present in Korean men with impaired spermatogenesis. Methods A total 170 Korean men with impaired spermatogenesis and 272 normal controls were screened. The coding regions including exon-intron boundaries of EGR4 were sequenced by PCR-direct sequencing method. Results We identified eight sequence variations in the coding region and 3'-UTR regions of the EGR4 gene. Four were nonsynonymous variants (rs771189047, rs561568849, rs763487015, and rs546250227), three were synonymous variants (rs115948271, rs528939702, and rs7558708), and one variant (rs2229294) was localized in the 3'-UTR. Three nonsynonymous variants [c.65_66InsG (p. Cys23Leufs*37), c.236C > T (p. Pro79Leu), c.1294G > T (p. Val432Leu)] and one synonymous variant [c.1230G > A (p. Thr410)] were not detected in controls. To evaluate the pathogenic effects of nonsynonymous variants, we used seven prediction methods. The c.214C > A (p. Arg72Ser) and c.236C > T (p. Pro79Leu) variants were predicted as "damaging" by SIFT and SNAP2. The c.65_66insG (p. Cys23Leufs*37) variants were predicted as "disease causing" by Mutation Taster, SNPs &GO and SNAP2. The c.867C > G (p. Leu289) variants were predicted as "disease causing" only by Mutation Taster. Conclusion To date, this study is the first to screen the EGR4 gene in relation to male infertility. However, our findings did not clearly explain how nonsynonymous EGR4 variations affect spermatogenesis. Therefore, further studies are required to validate the functional impact of EGR4 variations on spermatogenesis.